Diferentes estratégias no modelo de treinamento de força geram diferentes respostas morfológicas em modelos animais - Oliveira, Franciele Cristina Pereira de (2023)
Considering that the training protocols used in laboratory animals have only been replicated instead of being adjusted, this study aimed to compare the morphology and physiology of body composition in animal models submitted to two strength training protocols. For this, 15 male Wistar rats with 21 days of life were used. These were randomly distributed into 3 groups: Control Group (GC, n=4); Strength Group (GF, n=5); Resistance Group (GC, n=5). The animals were evaluated for body composition and subjected to familiarization with stair exercise for one week. After 24 hours of the last adaptation session, the Load Test was performed with caudal blood lactate collections. The animals were encouraged to perform resistance training for 8 weeks. The FG used protocol 25; 50; 75 and 100% + 30g of additional load in the last series, 5x a week with 2 minutes of recovery interval, while the RG was submitted to 5 weekly trainings, with 6 ascents at 50% of intensity and with intervals of up to 1 minute and 30 seconds. 48 hours after the intervention weeks, the animals were submitted to the last maximum load test and body composition evaluation. After the nalyzes and under anesthesia, the animals were euthanized and the tissues of the gastrocnemius, soleus, tibia, flexor hallucis longus muscles, in addition to the liver were dissected, weighed and measured. For descriptive statistical analysis, mean and standard deviation were applied. For inferential statistics, one-way ANOVA was adopted for comparisons before and after two-away ANOVA for comparison between groups. For post hoc analysis Bonferroni was used. When analyzing the characterization of the animals, it was possible to observe that there were significant differences between the GC and the RG and GF, with the GR having the greatest differences in terms of carcass weight and TA muscle; GF had greater differences in fat weight. When evaluating the bioelectric results, it was noted that the GF had higher TBW results and the GR in FFM. In the load test results, the GR had greater strength gains; As for the training density when compared to the beginning of the experiment, the GF had greater differences in the final weeks. Both exercised groups showed changes in post-exercise lactacidemia, with the GF having the greatest differences. The tissues of the FHL and TA muscles showed a lower amount of oxidative enzymes in the exercised groups. The groups submitted to the exercise presented higher AST of the muscular fiber compared to the CG, being the GF greater than the RG. In conclusion, it is possible to admit that different training strategies generate different physiological and morphological responses in animals submitted to different models of RT